PIACS: A System for the Automatic Detection, Categorization and Comparison of Scratch-Related Skin Lesions in Dermatology. - Bruland, Philipp; Hänse, Waldemar; Schedel, Fiona; Ständer, Sonja; Fritz, Fleur (Studies in health technology and informatics)
In the treatment of chronic pruritus-related, scratch-induced skin lesions the categorization, counting and temporal comparison are common methodologies. The observation requires a good memory and expertise in this field to gain comparable findings for this time-consuming process. Digital image processing aims at supporting such manual detections. The objective is to develop a software tool for automatic image detection and comparison. The new photographic setting implies the usage of markers to derive the brightness and size of lesions. MATLAB has been used for the software development. The newly defined setting allows taking standardized images of pruritus-associated cutaneous lesions for detection and comparison. The tool named PIACS (Prurigo Image Analyzing and Comparing System) allows automatically detecting, categorizing and comparing lesions based on digital images.